Investigation of the Effects of Epigallocatechin-3-Gallate on Caspase-3, IL-1?, IL-6, P53 and HO-1 Gene Expressions Against Cisplatin-Induced Pancreatic Tissue Injury in Rats - Arslan, Barak; Beyaz, Seda; Gok, Ozlem; Erman, Orhan; Ozercan, Ibrahim Hanifi; Aslan, Abdullah (Springer, 2024)
Cisplatin, which is used as a chemotherapy drug in some types of cancer, can cause DNA damage in cells and some organ damage after certain limits. Damage studies with cisplatin are mostly on organs such as the liver and lungs and some types of cancer. Damage studies on pancreatic tissue are relatively few, and they are especially related to insulin. In this study, the protective effects of epigallocatechin-3-gallate (EGCG), which has antioxidant and antitumor properties, were investigated against the general damage caused by cisplatin on the pancreatic tissue. A total of 28 male rats were used, divided into 4 groups, in the 4-week study. Cisplatin and EGCG were given intraperitoneally. Malondialdehyde, catalase and glutathione levels were measured spectrophotometrically. Caspase-3, IL-1 alpha, IL-6, p53, and HO-1 protein expressions were determined by the Western Blotting method. In addition, histopathological examination of the pancreatic tissue was performed and the findings were evaluated statistically. In our findings, a decrease in malondialdehyde levels and an increase in catalase activity and glutathione levels were observed in the pancreatic tissue in rat groups to which EGCG was administered. It was observed that the expression levels of IL-1 alpha, IL-6 proteins, which are markers of inflammation, were significantly decreased in the EGCG-treated group (EGCG+Cis) compared to the cisplatin group. In the histopathological examination, it was observed that pancreatic damage occurred significantly in the cisplatin-administered group and decreased in the treatment group. According to these data, it has been shown that treatment with EGCG can prevent toxicity in cisplatin-induced pancreotoxicity by providing an anti-inflammatory effect.
Keywords: cisplatin; EGCG; HO-1; pancreas; p53